Spanish adaptation and psychometric properties of the Relationship Belief Inventory in community samples from Spain and Mexico - Garcia-Zavala, Gabriela; de Irala, Jokin; Osorio, Alfonso; Martín-Lanas, Raquel; Cano-Prous, Adrián (Anales de Psicología / Annals of Psychology, 2026)
Identifying dysfunctional beliefs about romantic relationships is important for fostering healthy relationship dynamics. This study aimed to translate into Spanish and verify the psychometric properties of the Relationship Belief Inventory (RBI) in community samples from Spain and Mexico. A two-phase study was conducted: Phase I involved translation, while Phase II focused on psychometric analysis. The results showed that an 18-item scale considering only three beliefs (“Disagreement is destructive”, “Mindreading is expected”, and “Sexes are different”) fit better than the original proposal. Validity was also supported by correlations with neuroticism, relationship power imbalance, and parents’ relationship; as well as by group differences between clinical and community samples, and between men and women. Reliability was confirmed only for the three beliefs included in the final model. In conclusion, the validity and reliability of the Spanish version of the Relationship Belief Inventory (RBI-S) were sufficiently supported in this study.